Implementasi Algoritma Branch and Bound dalam Penentuan Jumlah Produksi untuk Memaksimalkan Keuntungan - Yusrah Nazari Firdaus; Nintia Litano Buyung; Agustira Hermansyah; Ranti Nurhadiyati; Ilham Falani; Elfitria Wiratmani (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
Optimal production planning in order to maximize profits, taking into account the limited resources they have. UKM Puguh Jaya is a mattress fabric convection business. There are several types of manufactured products including: 120 types of fabric, 140 types of fabric, the type of fabric 160. Production planning in SMEs can be seen as an integer programming model that aims to maximize profits, by determining the amount of production for each type and remember all the resources limited availability. The solution search for this model is done by the Branch and Bound algorithm. Based on the calculation results using QM software for Windows, it is known that the determination of the amount of production using branches and algorithms is bound to provide a profit increase of 18.7% compared to the profit from the previous UKM Puguh Jaya.